"Similar Souls on the Journey": Meaning-Making in a Contemplative Community of Faculty of Color - Jennifer L Pemberton (Adult Education Research Conference, 2018)
This paper highlights the meaning, both personal and professional, made by participants in a community of faculty of color, with a focus on contemplative practices and pedagogy.
Keywords: Contemplative pedagogy; learning community; faculty of color